Neuromodulation by mGluRs in Sound Localization Circuits in the Auditory Brainstem - Goel, Nupur; Peng, Kang; Lu, Yong (Frontiers in Neural Circuits, 2020)
The ability of humans and animals to localize the source of a sound in a complex acoustic environment facilitates communication and survival. The major cues used for sound localization at horizontal planes are interaural time and level differences (ITD and ILD), which are analyzed by distinct neural circuits in the brainstem. Here, we review the studies on metabotropic glutamate receptor (mGluR)-mediated neuromodulation of both intrinsic and synaptic properties of brainstem neurons in these circuits. Both mammalian and avian animal models have been used, with each having their advantages that are not present in the other. For the mammalian model, we discuss mGluR neuromodulation in the ILD circuit, with an emphasis on the recent discovery of differential modulation of synaptic transmission of different transmitter release modes. For the avian model, we focus on reviewing mGluR neuromodulation in the ITD pathway, with an emphasis on tonotopic distribution and synaptic plasticity of mGluR modulation in coincidence detector neurons. Future works are proposed to further investigate the functions and mechanisms of mGluRs in the sound localization circuits.